Poor compliance and increased mortality, depression and healthcare costs in patients with congenital adrenal hyperplasia. Issue 4 (April 2018) - Jenkins-Jones, Sara; Parviainen, Lotta; Porter, John; Withe, Mike; Whitaker, Martin J; Holden, Sarah E; Morgan, Christopher LI; Currie, Craig J; Ross, Richard J M
Abstract : Objectives: To evaluate the risks of depression and all-cause mortality, healthcare utilisation costs and treatment adherence in congenital adrenal hyperplasia (CAH) in the United Kingdom. Design and methods: A retrospective, matched-cohort study using UK primary-care data from the Clinical Practice Research Datalink linked to hospital and death certification data. Patients diagnosed with CAH and having ≥1 corticosteroid prescription were matched 1:10 to reference subjects. Risk of death and lifetime prevalence of depression were compared using Cox regression models. Direct financial costs were estimated for healthcare contacts. Treatment adherence was measured by medical possession ratio (MPR). Results: 605 patients with CAH were identified; 562 were matched. 270 CAH patients (2700 controls) were linkable to death-certificate data, with adjusted hazard ratio for all-cause mortality 5.17 (95% CI 2.81–9.50). Mean (s.d. ) age at death in CAH patients was 54.8 (23.9) vs 72.8 (18.0) years in control patients. The prevalence ratio of depression in CAH vs control patients was 1.28 (95% CI 1.13–1.45). Mean (s.d. ) annual healthcare costs were higher in CAH than controls: at age 0–6 years, £7038 (£14 846) vs £2879 (£13 972, P < 0.001); 7–17 years, £3766 (£7494) vs £1232 (£2451, P < 0.001); 18–40 years, £1539 (£872) vs £1344 (£1620, P = 0.007) and ≥41 years, £4204 (£4863) vs £1651 (£2303, P < 0.001). Treatment adherence was lowest in adults, with 141 (36%) of 396 eligible patients having an MPR <80%. Conclusions: This first analysis of CAH in routine UK healthcare suggests that patients with CAH have increased mortality, depression and healthcare utilisation and low treatment adherence.